Myśl i działalność społeczna biskupa Stanisława Adamskiego = The Thought and Social Work of Bishop Stanisław Adamski - Łętocha, Rafał 1973- (2010)
Bishop Stanisław Adamski was one of the most important activists and social thinkers of the Polish Catholic Church of the first half of the 20th century. He devoted the majority of his activity to organizing a cooperative movement and to propagating this kind of solution on Polish soil. For years he fulfilled the function of member of the board, and then chairman of the Union of Earnings and Economic Cooperatives, which was the headquarters of all Polish cooperatives in the Prussian partition. After Poland gained independence he saw in the cooperative movement an excellent way of creating a strong middle class in Poland, the third estate the lack of which had apparently had such an effect on the earlier fortunes of the country. In his work he also emphasised strongly the moral basis and psychological effects of this movement, stressing that it would be favourable to the development of various desired characteristics, attitudes and behaviours, and therefore fulfil an educational role.
Keywords: antropologia religii; badania porównawcze religii; filozofia religiistudia religiologica; historia religii; psychologia religii; Religia; Religijność; religioznawstwo; socjologii religii; wuj; wydawnictwo uj